2007
DOI: 10.1111/j.1600-079x.2007.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the keys to diurnality downstream from the circadian clock: role of melatonin in a dual‐phasing rodent, Octodon degus

Abstract: Melatonin is an essential component for circadian system function, whose daily plasma secretory rhythm is driven by the suprachiasmatic nucleus (SCN), contributing to the communication of temporal messages from the central circadian clock to all cells. Melatonin secretion peaks in the dark, regardless of whether animals are diurnal or nocturnal. To date, the precise mechanisms that explain how the circadian system is configured as nocturnal or diurnal remain unknown. The present study examines mid-day and midn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 42 publications
2
33
1
Order By: Relevance
“…To date, partially based on studies that indicate no differences between the nocturnal and diurnal pacemaker (Schwartz et al, 1983), it has been generally accepted that the switch from diurnal to nocturnal probably occurs downstream from the circadian pacemaker (Vivanco et al, 2007). This circumstance may have an adaptive value, because after this inversion the master clock may go on keeping time for a number of functions, such as synchronization with conspecifics, photoperiodic responses, anticipation to prey and predators, etc., whereas the timing of some specific behaviors, such as WRA, might be altered to cope with a particular need (e.g., to avoid overheating) without affecting others (Mrosovsky, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…To date, partially based on studies that indicate no differences between the nocturnal and diurnal pacemaker (Schwartz et al, 1983), it has been generally accepted that the switch from diurnal to nocturnal probably occurs downstream from the circadian pacemaker (Vivanco et al, 2007). This circumstance may have an adaptive value, because after this inversion the master clock may go on keeping time for a number of functions, such as synchronization with conspecifics, photoperiodic responses, anticipation to prey and predators, etc., whereas the timing of some specific behaviors, such as WRA, might be altered to cope with a particular need (e.g., to avoid overheating) without affecting others (Mrosovsky, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Lee episodes in the degus' daily activity patterns remained stable while the wheel-induced phase-switch occurred. We also note that, although the phase of core body temperature is altered by a wheel-induced phase switch, the timing of the nightly minimum in core temperature, prior to the morning crepuscular activity bout, appears to be unaffected (Kas & Edgar 1998, 1999Vivanco et al 2007). These data, in combination with evidence that the phase-response curves of animals with a diurnal and nocturnal entrained phase are the same (Kas & Edgar 2000), allow us to confidently argue that the circadian pacemaker of degus remains stably entrained to the LD cycle regardless of the instability of the phase of its activity output.…”
Section: Biological Rhythm Research 275mentioning
confidence: 93%
“…Although many experiments have examined degu circadian rhythms while the animals were displaying unimodal, day-active behavior (e.g., Refinetti 1996;Jechura et al 2000;Hummer et al 2007;Vivanco et al 2007), other studies have focused on conditions which induced bimodal, crepuscular, or even nocturnal activity patterns (Kas & Edgar 1998, 1999Garcia-Allegue et al 1999;Ocampo-Garces et al 2005;Ocampo-Garces et al 2006;Refinetti 2006). These studies are complementary for developing an understanding of the underlying mechanisms determining phase-preference in this species.…”
Section: Entrained Circadian Rhythms In the Laboratorymentioning
confidence: 97%
See 1 more Smart Citation
“…The results of the present study support the notion of elevated SWA as it was observed that SWA in NREM of the arrhythmic group was consistently higher when compared to the rhythmic group and this was seen in both light and dark periods; however, the results disagree with the notion of an increase in sleep duration as it was observed that the average duration of an episode of NREM in the arrhythmic group was significantly lower when compared to the rhythmic group. Interestingly, investigation of circadian chronotypes in the O. degus showed that differential responses to melatonin do not induce distinct circadian chronotypes [Vivanco et al, 2007], yet scheduled feeding can induce differing patterns of rhythmicity [Vivanco et al, 2010], but assessment of locomotor activity yielded the most significant distinction of circadian chronotypes [Vivanco et al, 2009]. It has been shown that TST in the O. degus amounts to 37.6 8 3.7% per 24 h [Kas and Edgar, 1998], though it is unclear whether the patterns of sleep and wake are different between circadian chronotypes of the O. degus .…”
Section: Circadian Rhythmicity and Sleepmentioning
confidence: 99%